2020
DOI: 10.1002/dvdy.249
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of epidermal stratification during post‐larval development in zebrafish

Abstract: Background The epidermis, as a defensive barrier, is a consistent trait throughout animal evolution. During post‐larval development, the zebrafish epidermis thickens by stratification or addition of new cell layers. Epidermal basal stem cells, expressing the transcription factor p63, are known to be involved in this process. Zebrafish post‐larval epidermal stratification is a tractable system to study how stem cells participate in organ growth. Methods We used immunohistochemistry, in combination with EdU cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Thus, we began by examining keratinocyte contributions to debris removal in adult skin. The epidermis stratifies during post-larval growth, adding layers of suprabasal cells in between the periderm and basal cell layers ( Guzman et al, 2013 ; Rangel-Huerta et al, 2021 ). In adult scales, somatosensory axons arborize throughout basal and suprabasal epidermal layers, often in direct contact with keratinocytes ( Rasmussen et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we began by examining keratinocyte contributions to debris removal in adult skin. The epidermis stratifies during post-larval growth, adding layers of suprabasal cells in between the periderm and basal cell layers ( Guzman et al, 2013 ; Rangel-Huerta et al, 2021 ). In adult scales, somatosensory axons arborize throughout basal and suprabasal epidermal layers, often in direct contact with keratinocytes ( Rasmussen et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…To characterize the molecular and cellular properties of regenerating dMCs, we focused on 5 dpp, a timepoint that contains a mix of dMCs and MCs ( Figure 2K ). We first assayed expression of Tp63, a transcription factor critical in epidermal development and highly expressed in basal keratinocytes (Bakkers et al, 2002; Guzman et al, 2013; Lee and Kimelman, 2002; Rangel-Huerta et al, 2021) ( Figure 3B, asterisks ). Immunostaining revealed that MCs did not express detectable levels of Tp63 ( Figure 3A-A’ ).…”
Section: Resultsmentioning
confidence: 99%
“…As the skin expands during post-larval growth, it undergoes two major morphogenetic changes. First, the bilayered epidermis begins to stratify through the proliferation of the Tp63-positive basal cell layer (Guzman et al, 2013;Rangel-Huerta et al, 2021). As the skin stratifies, the larval periderm is sloughed off and replaced by basal cell derivatives (Lee et al, 2014).…”
Section: Reriomentioning
confidence: 99%